A new species of Phyllonorycter (Lepidoptera: Gracillariidae) from Kenya discovered by using the sex attractant Z8-tetradecen-1-yl acetate - de Prins, Jurate; Moz‚Raitis, Raimondas (Zootaxa, 2006)
Phyllonorycter obandai, new species, was discovered in Kenya using traps baited with the synthetic sex attractant Z8-tetradecen-1-yl acetate. This is the first species of Phyllonorycter recorded from Kenya. External morphological features of adult males, along with their genitalia are described and illustrated from specimens attracted to the traps. A distribution map for P. obandai is also presented.